Reporting on climate solutions in institutional, Indigenous, and climate-focused news outlets - Barchas-Lichtenstein, Jay; Voiklis, John; Attaway, Bennett; LaMarca, Nicole; Sawdy, Rachel; Vasquez, Sky; Parson, Patti; Bennett-Begaye, Jourdan (Frontiers in Communication, 2026)
This study focuses on the portrayal of climate problems, climate solutions, and climate problem-solvers across several types of U.S. news outlets, with particular attention to representation of Indigenous peoples. We sample coverage of strategies to address climate change from institutional, climate-focused, and Indigenous-focused news outlets, and analyze how stories frame problems, solutions, and the people responsible for and affected by them. We find that climate-focused and institutional news coverage of climate solutions is broadly similar, but both differ significantly from Indigenous journalism. Indigenous journalism is more likely to present benefits of solutions (rather than only harms they aim to prevent), consider holistic solutions that address both adaptation and mitigation, identify victims of climate change, focus on Indigenous people in all roles, and highlight traditional knowledge. We close with discussion of how institutional news outlets might incorporate these perspectives to challenge their audiences’ stereotyped knowledge around climate problems, solutions, and problem solvers.